Editor's Choice – Endurant Stent Graft in Patients with Challenging Neck Anatomy "One Step Outside Instructions for Use": Early and Midterm Results from the EAGLE Registry. (December 2022) - van Basten Batenburg, Michael; 't Mannetje, Yannick W.; van Sambeek, Marc R.H.M.; Cuypers, Philippe W.M.; Georgiadis, George S.; Sondakh, Arthur O.; Teijink, Joep A.W.; ,
Abstract : Objective: The aim of the Endurant for Challenging Anatomy: Global Experience (EAGLE) registry is to evaluate prospectively the technical and clinical success rate of a stentgraft used in patients with challenging neck anatomy outside the instructions for use (IFU) but within objective anatomical limits. Methods: This was a prospective, international, multicentre, observational study. From 1 February 2012 to 1 September 2017, patients with an abdominal aortic aneurysm with a challenging infrarenal neck that were deemed suitable for endovascular aneurysm repair were included prospectively at 23 European centres. Patients were distributed by anatomy into three groups: short neck (SN; infrarenal neck 5 – 10 mm in combination with suprarenal angulation [α] ≤ 45° and infrarenal angulation [β] ≤ 60°); medium neck (MN; infrarenal neck 10 – 15 mm with α ≤ 60° and β 60° – 75° or α 45°– 60° and β ≤ 75°; and long angulated neck (LN; infrarenal neck ≥ 15 mm with α ≤ 75° and β 75°– 90° or α 60°– 75° and β ≤ 90°. All computed tomography scans were reviewed by an independent core laboratory. Primary outcomes were technical and clinical success. Secondary endpoints were peri-operative major adverse events, all cause mortality, aneurysm related mortality, endoleaks, migration, and secondary intervention. Results: One hundred and fifty patients (81.3% male) were included (SN = 55, MN = 16, LN = 79). The median follow up was 36 ± 12.6 months. In the overall cohort, the technical success rate was 93.3%. Estimated freedom from aneurysm related death was 97.3% at three years. Freedom from secondary interventions was 84.7% at three years. Estimated clinical success was 96.0%, 90.8%, and 83.2% at 30 days, one year, and three years, respectively. Estimated freedom from all cause mortality, late type IA endoleak, and migration at three years was 75.1%, 93.7%, and 99.3%, respectively. Conclusion: The early and midterm results of the EAGLE registry show that endovascular repair with the Endurant stentgraft in selected patients with challenging infrarenal neck anatomy yields results in line with large "real world" registries. Long term results are awaited for more definitive conclusions.